Antioxidant, antimicrobial and total phenolic contents of Calophyllum symingtonianum - Nissad, Attoumani; Darnis, Deny Susanti; Bakhtiar, M. Taher (Coastal Life Medicine Media co., Limited, 2013)
Objectives: To determine the total phenolic content, antioxidant and antimicrobial activities of the extracts from Calophyllum symingtonianum. Methods: The extracts were tested for their antioxidant activity by the DPPH radical scavenging assay and the β-carotene bleaching assay, while the antimicrobial activity was determined by disc diffusion method. Results: All the tested extracts showed antioxidant and antimicrobial properties. The extracts showed moderate antimicrobial activity against S. aureus with zone of inhibition values of 10, 11 and 12 mm for n-hexane, DCM and methanol extracts respectively at 30 µg/disc. n-Hexane showed low antimicrobial activity against P. aeruginosa (5 mm) at 30 µg/disc. The total phenolic test showed that methanol has high phenolic content (162.25 mg GAE/g of extract) compared to the other extracts. Conclusion: The ability of the extracts to inhibit microbial growth at a concentration of 30 µg/disc indicated the its potent antimicrobial activity.